2018
DOI: 10.1620/tjem.246.141
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid Sarcoma of the Paranasal Sinuses in a Patient with Acute Myeloid Leukemia

Abstract: Myeloid sarcoma (MS) is an uncommon extramedullary malignant tumor, and often represents a subgroup of acute myeloid leukemia (AML). MS of paranasal sinus origin is extremely rare. We report an uncommon case of sinonasal MS associated with AML, who was successfully treated with hematopoietic stem-cell transplantation. A 39-year-old male was admitted with complaints of left nasal obstruction and proptosis. Computed tomography and magnetic resonance imaging identified a left ethmoidal mass involving the maxillar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 20 publications
0
16
0
1
Order By: Relevance
“…We present a literature review of proptosis secondary to sinonasal masses in Table 1 [11][12][13][14][15][16]. To the best of our knowledge, the present case report is the first documented instance of a sinonasal mass causing ocular symptoms exclusively on the contralateral side.…”
Section: Discussionmentioning
confidence: 99%
“…We present a literature review of proptosis secondary to sinonasal masses in Table 1 [11][12][13][14][15][16]. To the best of our knowledge, the present case report is the first documented instance of a sinonasal mass causing ocular symptoms exclusively on the contralateral side.…”
Section: Discussionmentioning
confidence: 99%
“…Although MS represents an extramedullary proliferation and may occur at nearly any anatomic site, MS involvement in the sinonasal area is rare. Suzuki et al [ 5 ] summarized 10 sinonasal MS cases that had been reported between 2000 and 2018, including 9 adults and 1 child. Holsinger et al [ 6 ] found 2 pediatric sinonasal MS cases recorded between 1955 and 1999 at university-based, tertiary care referral centers in Houston.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] However, the sinonasal area may be a predilection site of isolated MS occupied 20% of sinonasal MS cases. [ 5 ] MS has a wide age distribution and pediatric population is a preference age group. [ 3 ] Nevertheless, some retrospective series suggested the main age range of onset of MS is connected with tumor site to some extent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiotherapy (RT) including radioisotope therapy (RIT) and external beam radiotherapy (EBRT) have been widely applied in clinic for cancer treatment . In order to improve the therapeutic efficiency of cancer, RT usually combines other therapies such as chemotherapy, photothermal therapy, or surgery for cancer treatment, further increasing the cure rate . In recent years, various nanomaterials with radioisotope labeling/doping have been used for tumor imaging and combination of RIT and photothermal therapy, realizing great well cancer treatment .…”
Section: Introductionmentioning
confidence: 99%